102k views
5 votes
For the function f defined by f(x)=x^2+2x+3 find f(−x),−f(x) , and −f(−x).

User John Dobie
by
5.9k points

1 Answer

2 votes

Hello from MrBillDoesMath!


Answer:

See discussion below


Discussion:

A real brain teaser!

If f(x) = x^2 + 2x + 3, then

a. f(-x) = (-x)^2 + 2(-x) +3

= x^2 -2x + 3


b. - f(x) = - (x^2 + 2x + 3) = -x^2 -2x - 3


c. Using a) above

-f(-x) = - (x^2 -2x + 3 ) = -x^2 + 2x - 3


Note that f(x) is not an even function ( f(x) = f(-x) ) or an odd function ( f(-x) = - f(x))



Thank you,

MrB

User Jels Boulangier
by
5.7k points